Building Sustainable Industrial Areas: Experience and Perspectives from the Mediterranean and Western Balkan Countries - Preka, R.; Tarantini, M.; Dominici Loprieno, A.; Litido, M.; Segreto, M. (European Journal of Sustainable Development, 2013)
An EU research project (Mediterranean Eco-Industrial Development, (MEID)) whichinvolves different actors from Mediterranean and Western Balkans region, is currently inprogress. Its general objective is to provide innovative management figures and a decisionsupport tool (model) to plan, build and manage more competitive Sustainable IndustrialAreas (SIA) in the involved region.In order to correspond to a coherent solution, an accurate research has been performed.The methodology implemented to detect the main issues under survey has been a SWOTanalysis of several target IAs.Following its results, there have been defined the most relevant aspects aiming atsustainability of IAs in the area. The model introduces or encourages the continuousimprovement of environmental performances of the Mediterranean industrial areas in thefollowing fields: integrating production and dismissal of solid wastes, energy saving anduse of renewable energies, reducing water consumption, better viability and avoid thedeposit of dangerous material. Thanks to this “green approach”, SMEs will be the finalbeneficiaries, fostered to eco-innovation, competitiveness and transnational cooperation.This paper presents the general context and results of the MEID project.